A Content Analysis of Moral Principles in "English for Nusantara" Textbook - Abas, Totoh Tauhidin; Apriant, Mifta Ireza Nur; Rahmawati, Maya (Jurnal Ilmiah Wahana Pendidikan, 2023)
Quality education can improve the quality of human resources. Moral education for students is essential to improve their quality of life. Moral learning in the ELT context can help students to develop their personality and positive relationships with others. Consequently, the researcher aims to examine the moral values in the English learning textbook "English for Nusantara," designed for 7th-grade students. This study employs a qualitative approach, employing a content analysis design for its methodology. This research was conducted using the moral criteria proposed by Michele Borba. The results showed that all components of moral values appeared in the students' textbooks. The most dominant moral learning is about self-control representing 28.36%, while the lowest moral value is Conscience representing 4.48%. Each of these moral values is related to one another because if one of them arises, the affective of other students will emerge from the components of the moral values of other students. The findings of this study support students to become individuals with integrity.